Bringing the world back in: Revolutions and relations before and after the quantum event. (October 2020) - Grove, Jairus
Quantum physics is being positioned as a new archive for addressing major theoretical problems in the field of international relations. Two of the major proponents of engaging quantum thinking within international relations, James Der Derian and Alexander Wendt, have argued that quantum thinking offers the possibility of a major paradigm shift in the field. Before we determine quantum's revolutionary potential, the persistent and most pressing question for me is how to position quantum thinking among other kinds of and claims to knowledge. I want to horizontalize where different kinds of knowledge sit within the renewed attention to quantum theory. Rather than just horizontalize or flatten ontology, I want to see what happens when we place scientific and philosophical inquiry in dialogue, and what that conversation does to the authority and value of quantum thinking for the social sciences. The article reconstructs the dialogue between the first generation of quantum physicists and the philosophers who informed them. Rather than make an explicit argument about the philosophical debt of physics, I argue that a broad and highly interdisciplinary set of questions drove both fields well beyond the specific areas of expertise of any of these thinkers. I believe this adventure of ideas followed by physicists, philosophers, and social theorists alike offers us a way forward as the complexity of our contemporary global challenges confront us now with the necessity to think well beyond our disciplinary expertise.